Zwischen Traditionalismus und Modernisierung: Musikausbildung in Russland - Irina Susidko; Pavel Lutsker (Musica Docta)
Music education in Russia is currently experiencing a period of calm and isolation rather than one of controversy and discussion. In the West, the impetus for the current exchange of opinions in society has come from an active process of reassessment of values. In Russia, in recent years, initiatives in this area have been concentrated mainly in the hands of the state. It is understandable that the leading trend on the part of the state is rather conservative, if not ultra-conservative. However, such an exotic field as music education is largely left out of such initiatives. Moreover, the stages of modernisation and traditionalism in Russia and the West seem to proceed at their own pace and often do not coincide. We experienced such a period of modernisation relatively recently, in the 1990s and early 2000s, after the fall of the Iron Curtain. Today the majority of educators, researchers and active artists are suspicious of any ideologically motivated point of view, because in the past many in Russia had to suffer under the hegemony of ideological intolerance. The system of music education in Russia dates back to the 1920s and is still in place almost unchanged. It provides access to music education for a wide range of people and aims to teach a musical profession (mostly performance), although only a small percentage of students end up becoming musicians. Music education is based on a comprehensive basic course in the history of Western European and Russian musical culture (in several stages from primary school to higher education), as well as in theoretical and practical music disciplines. The history course is compulsory and, especially during the period of modernisation in 1990-2000, was considerably expanded and enriched with early and modern music. This position remains firmly established in the training of all musical specialities: pianists, orchestral musicians, musicologists, ethnomusicologists, musicians on folk instruments and even pop musicians. Of course, this picture of blissful conservatism is not without its problems. Firstly, it is maintained not so much by inner conviction as by inertia. Second, it is subject to erosion. Attempts are being made to reduce the primary school programme to mere familiarisation with playing instruments and basic training. In high school, the position of the Ministry of Education is followed, which aims to simplify the basic curriculum and give priority to more fashionable applied disciplines. Today, there is still a chance to redress the balance, but the situation in the near future looks very uncertain.